Gender‐based outcomes of bivalirudin versus heparin in patients undergoing percutaneous coronary interventions: Meta‐analysis of randomized controlled trials. Issue 5 (24th March 2017) - Mina, George S.; Firouzbakht, Tina; Modi, Kalgi; Dominic, Paari
Abstract : Objectives: We aimed to perform a gender‐based meta‐analysis of the outcome of bivalirudin versus heparin in patients undergoing percutaneous coronary interventions (PCI). Background: Bivalirudin has been shown to decrease major bleeding when compared to heparin ± glycoprotein IIb/IIIa inhibitors (GPI) in patients undergoing PCI. It is unclear, however, if those differences in outcomes are the same for men and women. Methods: We included randomized controlled trials (RCTs) that compared bivalirudin to heparin with or without GPI in patients undergoing PCI and reported outcome data that were stratified by gender. Random effect model was used to pool odds ratio (OR) and 95% confidence intervals (CI). Results: We included 9 trials with 33, 224 patients. Bivalirudin decreased major bleeding when compared to heparin plus routine GPI in both men (OR: 0.51, P  < 0.001) and women (OR: 0.55, P  < 0.001). However, when GPI were used selectively with heparin, the bleeding lowering effect of bivalirudin was statistically significant in men (OR: 0.69, P  = 0.02) but not in women (OR: 0.71, P  = 0.21). When compared to heparin ± GPI, there was a nonstatistically significant trend toward lower all‐cause mortality with bivalirudin in both men (OR: 0.76, P  = 0.055) and women (OR: 0.79, P  = 0.21). There were no significant differences in major adverse cardiovascular events between heparin and bivalirudin in both men and women. Conclusion: Bivalirudin decreases major bleeding in both men and women when compared to heparin plus routine GPI. However, when compared to heparin alone, the bleeding lowering benefit of bivalirudin is less evident in women. © 2017 Wiley Periodicals, Inc.